Main problems of the executive production system in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2019)
Abstract. The main problems of executive system of the Republic of Kazakhstan are analyzed in this article. Gapsof legislation in executive manufacture are considered. The reasons of untimely execution of executive documentsare established. The problem questions arising in the course of execution are investigated by judicial performers ofexecutive documents. And also solutions from the revealed problems are offered.Keywords. Legislation in executive manufacture, judicial performers, executive documents, debtors, court.